Knowledge About HIV/AIDS and Its Transmission and Misconception Among Women in Bangladesh - Jahar Bhowmik; Raaj Kishore Biswas (Kerman University of Medical Sciences, 2022)
Background  Asian and pacific region countries are high risk countries for human immunodeficiency virus/ acquired immune deficiency syndrome (HIV/AIDS). Although the prevalence of HIV/AIDS is low in Bangladesh but women in Bangladesh have been identified as susceptible due to associated socioeconomic exposures. There are various misconceptions associated with HIV/AIDS transmission among the women in low- and middle-income countries including Bangladesh, which lead to a negative attitude towards the HIV/AIDS-infected. The purpose of this study was to assess the overall knowledge, transmission, and misconception about HIV/AIDS among the women in Bangladesh as well as its spatial distribution across the country.Methods  The study used data from the UNICEF (United Nations Children's Fund) Multiple Indicator Cluster Survey (MICS) 2019, with a sample of 64 346 women. This was a cross-sectional, population-based survey of Bangladeshi women aged 15-49 conducted using a multistage, cluster sampling technique. Three binary outcome variables considered were knowledge about HIV/AIDS, knowledge about HIV/AIDS transmission and knowledge on myths and misconceptions on HIV/AIDS along with 10 predictors based on past literature. Bivariable analysis using chi-square tests of association was conducted to examine the unadjusted percentage differences of the outcome variables for each of the predictor variables and their associations. Multiple binary logistic regression models were then fitted to evaluate the association between the outcome variables and the predictors after adjusting for survey cluster, strata, and weights. All analysis was conducted in R software (V 2.5.0).Results  The percentage of women who held knowledge about HIV/AIDS, knowledge about HIV/AIDS transmission and knowledge on misconceptions about transmission of HIV were on average 60.3%, 52.2% and 71.7% respectively. The models indicated that women regularly exposed to media were 79%, 18% and 19% significantly more likely (odds ratio, OR: [95% CI] = 1.79: [1.70, 1.89]; 1.18: [1.10 1.26] and 1.19: [1.11, 1.27]) to have heard about HIV, aware about HIV transmission, and have less misconceptions about HIV respectively compared to those who were not exposed to media. Overall results indicate that women from peripheral districts living far from metropolitan cities were most unaware of HIV and had higher misconceptions about AIDS.Conclusion  The findings of this study should assist policy-makers and program implementers to focus on raising awareness to educating women about how HIV/AIDS is transmitted. Furthermore, interventions should be made by targeting the most disadvantaged groups, including younger women with low education living in rural areas, from poor households and limited access to information. Also, education on HIV transmission in Bangladesh should integrate cultural and ethnic considerations of HIV/AIDS.